An enabling framework for master-worker applications on the Computational Grid - Goux, J.-P.; Kulkarni, S.; Linderoth, J.; Yoder, M. (High Performance Distributed Computing (HPDC-9, 2000): 9th IEEE International Symposium, 2000)
Describes MW (Master-Worker) - a software framework that allows users to quickly and easily parallelize scientific computations using the master-worker paradigm on the Computational Grid. MW provides both a "top-level" interface to application software and a "bottom-level" interface to existing Grid computing toolkits. Both interfaces are briefly described. We conclude with a case study, where the necessary Grid services are provided by the Condor high-throughput computing system, and the MW-enabled application code is used to solve a combinatorial optimization problem of unprecedented complexity.